2015
DOI: 10.1371/journal.pone.0122149
|View full text |Cite
|
Sign up to set email alerts
|

Functional EpoR Pathway Utilization Is Not Detected in Primary Tumor Cells Isolated from Human Breast, Non-Small Cell Lung, Colorectal, and Ovarian Tumor Tissues

Abstract: Several clinical trials in oncology have reported increased mortality or disease progression associated with erythropoiesis-stimulating agents. One hypothesis proposes that erythropoiesis-stimulating agents directly stimulate tumor proliferation and/or survival through cell-surface receptors. To test this hypothesis and examine if human tumors utilize the erythropoietin receptor pathway, the response of tumor cells to human recombinant erythropoietin was investigated in disaggregated tumor cells obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…In our hands EPO did not affect cell proliferation of PBMC and both types of malignant colon cells. This observation is in line with those by Neuman et al [16] who did not detect any effect of EPO on the number of polymorphonuclears and monocytes in dialysis patients and by Patterson et al [17] who did not obtain any proliferation of tumor cells from 186 patients with various cancers under the effect of EPO. The authors concluded that there are not EPO receptors at least on the tumor cells examined.…”
Section: Discussionsupporting
confidence: 92%
“…In our hands EPO did not affect cell proliferation of PBMC and both types of malignant colon cells. This observation is in line with those by Neuman et al [16] who did not detect any effect of EPO on the number of polymorphonuclears and monocytes in dialysis patients and by Patterson et al [17] who did not obtain any proliferation of tumor cells from 186 patients with various cancers under the effect of EPO. The authors concluded that there are not EPO receptors at least on the tumor cells examined.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these clinical observations, cell culture and animal model studies detected EPOR expression in and direct EPO actions on cancer cells, proposing a role for EPO signaling in promoting their viability, proliferation, metastatic potential, therapy resistance and stemness (11)(12)(13)(14)(15)(16). Evidence against a direct effect of EPO on cancer cells also exists (17,18), leaving the mechanism for EPO function in cancer still under debate.…”
mentioning
confidence: 68%
“…IGF-1R is an important receptor widely expressed at cell surfaces; it regulates the growth, proliferation, and apoptosis of cells through its combination with its ligands in target insulin-like growth factor (IGF) receptor proteins [ 20 ]. At present, relatively few researchers are focused on whether target insulin-like growth factor (IGF) receptor proteins coordinate with microRNA to regulate cell growth and apoptosis [ 21 , 22 ]. This article indicated that the over-expression of miRNA-323-5p reduced IGF-1R level.…”
Section: Discussionmentioning
confidence: 99%